Ethylene combustion performance with varying the N2 content in a porous burner. (1st January 2023) - Ling, Zhongqian; Lu, Ling; Zeng, Xianyang; Kuang, Min; Ling, Bo; Gao, Chuanji; Zhou, Chao
Abstract: Direct emissions of volatile organic compounds (VOCs) not only pollute the environment, but also waste a lot of resources. To overcome above problem, this paper creatively proposed the solution by porous media combustion technology. In this study, ethylene with different N2 content levels of 10%, 30%, and 50% (used to simulate VOCs) was experimentally burned in a self-designed porous medium burner stacked with 9 mm alumina balls. The effects of equivalence ratio, premixed gas flow velocity and dilution ratio on flammable region, maximum combustion temperature, combustion wave velocity, pollutant emissions and combustion treatment efficiency were investigated. The maximum combustion temperature increased with the equivalence ratio and the premixed gas flow velocity. Consequently, the corresponding combustion treatment efficiency increased and CO emissions decreased. With increasing the dilution ratio, the flammable region, maximum combustion temperature, and combustion treatment efficiency became smaller but CO emissions and the combustion wave velocity became larger, except the case with 10% N2 content in which combustion was better than that with pure ethylene. In general, with relatively higher φ ( φ  ≥ 0.50), medium V fv ( V fv ≥ 0.50), and appropriate α ( α  = 10%), the premixed gas could burn well with high combustion treatment efficiency. Highlights: ►Burning fuel-lean C2 H4 in a porous burner stacked with alumina balls. ►Exploring the flammable region and flame propagation characteristics of transient combustion. ►Uncovering the relationship between combustion wave and premixed flow velocities. ►Comprehensively considering pollutant emissions and C2 H4 treatment efficiency.